Poems and plays / by William Hayley, Esq. - Hayley, William, 1745-1820. (Tufts University. Tisch Library., 2015)
A new edition.; Volume 5 of 6.; 1 online resource (6 volumes); Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.